Kanker Leher Rahim (Cancer Cervix) Sebagai Pembunuh Wanita Terbanyak Di Negara Berkembang - Susilawati, Wulandari Dewi (Research of Service Administration Health and Sains Healthys, 2023)
Worldwide, cervical cancer is twelfth most common (Edward, 2010)   and the fifth most deadly cancer in women (Globocan, 2002). It affects about 16 per 100,000 women per year and kills about 9 per 100,000 per year (WHO, 2006). Approximately80% of cervical cancers occur in developing countries (Kent, 2010). Worldwide, in2008, it was estimated that there were 473,000 cases of cervical cancer, and 253,500 deaths per year (NCC, 2008).Cervical  cancer  is  the  leading  cause  of  cancer  death  in  most  developing countries (Edianto, 2006). Counted as many as 510,000 new cases occur each years and lasts more than 288,000 deaths from the disease worldwide. Low incidence of this disease in women aged under 25 years old, but the incidence increases in women aged35 to 40 years and reached a maximum at the age of the 50's. Meanwhile, the incidence of cervical cancer it self continues to increase from about 25 per 100,000 in 1988 to around 32 per 100,000 in 1992 (Edianto, 2006).In 2005, the number of women aged 15-64 years in Indonesia is 65 million and the prevalence of cervical cancer is 50 per 100,000 women. This means the number of patients with cervical cancer is approximately 32 500 patients. Patients with stage I as much as 7% or 2275, stage Ib-IIa by 28% or 9100, and a stage IIB-IV by 65% or 21125 patients (Rasjidi, 2007). This data showed that cancer cervix detected mostly on late stages, so it commonly called silent diseases.The uterine cervix is the lowest portion of a woman's uterus (womb). Most of the uterus lies in the pelvis, but part of the cervix is located in the vagina, where it connects the uterus with the vagina.Cancer of the cervix occurs when the cells of the cervix change in a way that leads to abnormal growth and invasion of other tissues or organs of the body. Like all cancers, cancer of the cervix is much more likely to be cured if it is detected early and treated immediately. One of the key features of cervical cancer is its slow progression from normal cervical tissue, to precancerous (or dysplastic) changes in the tissue, toinvasive cancer. The slow progression through numerous precancerous changes is very important because it provides opportunities for prevention and early detection and treatment.Invasive cancer means that the cancer affects the deeper tissues of the cervixand may have spread to other parts of the body. This spread is called metastasis. Cervical cancers don't always spread, but those that do most often spread to the lungs, the liver, the bladder, the vagina, and/or the rectum. Invasive cancer this way could caused death.This  literature  review  is  intended  to  improve  the  understanding  of  cervical cancer that is expected to impact on improving health services in particular increased levels of knowledge about cervical cancer and its prevention at an early stage to reduce the incidence of cervical cancer and the death because of it, especially in Indonesia.